GSDMD-dependent pyroptotic induction by a multivalent CXCR4-targeted nanotoxin blocks colorectal cancer metastases - Rita Sala; Elisa Rioja-Blanco; Naroa Serna; Laura Sánchez-García; Patricia Álamo; Lorena Alba-Castellón; Isolda Casanova; Antonio López-Pousa; Ugutz Unzueta; María Virtudes Céspedes; Esther Vázquez; Antonio Villaverde; et al. (Taylor & Francis Group, 2022)
Colorectal cancer (CRC) remains the third cause of cancer-related mortality in Western countries, metastases are the main cause of death. CRC treatment remains limited by systemic toxicity and chemotherapy resistance. Therefore, nanoparticle-mediated delivery of cytotoxic agents selectively to cancer cells represents an efficient strategy to increase the therapeutic index and overcome drug resistance. We have developed the T22-PE24-H6 therapeutic protein-only nanoparticle that incorporates the exotoxin A from Pseudomonas aeruginosa to selectively target CRC cells because of its multivalent ligand display that triggers a high selectivity interaction with the CXCR4 receptor overexpressed on the surface of CRC stem cells. We here observed a CXCR4-dependent cytotoxic effect for T22-PE24-H6, which was not mediated by apoptosis, but instead capable of inducing a time-dependent and sequential activation of pyroptotic markers in CRC cells in vitro. Next, we demonstrated that repeated doses of T22-PE24-H6 inhibit tumor growth in a subcutaneous CXCR4+ CRC model, also through pyroptotic activation. Most importantly, this nanoparticle also blocked the development of lymphatic and hematogenous metastases, in a highly aggressive CXCR4+ SW1417 orthotopic CRC model, in the absence of systemic toxicity. This targeted drug delivery approach supports for the first time the clinical relevance of inducing GSDMD-dependent pyroptosis, a cell death mechanism alternative to apoptosis, in CRC models, leading to the selective elimination of CXCR4+ cancer stem cells, which are associated with resistance, metastases and anti-apoptotic upregulation.